Pemanfaatan Metode “Gasing” Dalam Pembelajaran Matematika Yang Bermakna Dan Menyenangkan Di Gugus Ii Kecamatan Bebandem - Mahayukti, Gusti Ayu; Yudiana, I Kadek Edi; Silalahi, Raphita Yanisari; Putri, Ni Putu Ratih Diana; Restiawan, I Made Aditya Natha; Artayani, Ni Nyoman Tri (LPPM Universitas Pekalongan, 2024)
This community service was carried out due to concern about the psychological trauma experienced by students in Gugus II Bebandem caused by frequent natural disasters (volcanic eruption), which have led to a decline in students’ understanding of mathematics. Considering the limited conditions and situation, the solution to address this issue is to utilize the GASING method (Gampang, Asyik, and Menyenangkan) in meaningful and enjoyable mathematics learning in the Gugus II area of Bebandem District. The education and training conducted have successfully addressed the existing problems. This is evidenced by: (1) Teachers participated fully and enthusiastically in the activities until the end of the activity, as indicated by an overall attendance rate of 100% and participant activity during the training at 98.2%, categorized as very active; (2) The results of the teacher response questionnaire to the activities showed a positive percentage of 93.7%; and (3) It was conclude that the GASING method is highly suitable for implementation in the mathematics learning of Gugus II Bebandem.